ANALISIS MANAJEMEN PERSEDIAAN ALAT KOLAM RENANG DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) DI PT.XYZ - Steven Saut (2023)
PT.XYZ is a retail company specializing in the sale of swimming pool goods. The company frequently encounters issues of oversupply. Upon closer examination, it is evident that the inventory remains stagnant due to the absence of an effective system for managing and optimizing its use. It is crucial for the company to enhance its inventory management and procurement strategies in order to reduce inventory costs, enhance customer service, and improve overall operational efficiency. This study will primarily concentrate on products categorized as A in the ABC method, which are known for their consistent and high demand, making them particularly significant to the company. The research aims to utilize the EOQ method to optimize the procurement and ordering processes. Consequently, the ABC Analysis revealed that there were a total of 20 products classified as A. By applying the EOQ method on VH 30FT/9M product, the company achieved a remarkable 44% cost savings compared to its existing approach. To guide the company for the upcoming one-year period (January 2023 to December 2023), the following strategy details for VH 30FT/9M is proposed: an EOQ of 1055 units, a reorder point of 97 units, and a safety stock of 59 units. These recommendations are projected to result in an estimated total inventory cost of Rp 8,101,222 for the duration of one year.